How does Testosterone Therapy Impact Quality of Life and Cancer Recurrence Rates in High-Risk Prostate Cancer Survivors? : A Systematic Review - Salman Alfarisi Kuddah; John M. Sangkai (The International Journal of Medical Science and Health Research, 2025)
Introduction: The use of testosterone therapy (TRT) to manage hypogonadal symptoms in prostate cancer survivors is clinically contentious due to long-standing fears that it may promote cancer recurrence. Definitive treatments often lead to debilitating side effects like fatigue and loss of libido, creating a dilemma between improving quality of life (QoL) and ensuring oncological safety. This systematic review evaluates the impact of testosterone therapy on biochemical recurrence rates and QoL in high-risk prostate cancer survivors. Methods: Following PRISMA 2020 guidelines, a systematic search was conducted across PubMed, Springer, Google Scholar, and Semantic Scholar for studies published since 2015. Eligibility criteria targeted randomized controlled trials and prospective cohort studies assessing TRT in adult males after primary treatment for high-risk prostate cancer, with outcomes of cancer recurrence and/or QoL. After screening 763 records, 19 studies were included in the final analysis. Results: The synthesized evidence did not show a significant increase in biochemical recurrence with TRT. Several studies reported low recurrence rates, with one frequency-matched study finding that TRT was associated with a 1.4-year delay in recurrence. Conversely, a critical deficiency in QoL data was identified; 16 of the 19 included studies did not use validated assessment tools to measure patient-reported outcomes. Reported adverse events were generally low-grade and manageable. Conclusion: A notable discordance exists between the emerging oncological safety of TRT and the profound lack of evidence supporting its benefits for QoL in high-risk prostate cancer survivors. While the historical fear of cancer recurrence is not strongly supported by recent data, the therapy's actual benefit to patients remains largely unquantified. Future research must prioritize QoL as a primary endpoint to establish a definitive risk-benefit profile.